Dimensions of perforator flaps on the lower leg depending on localization. Issue 7 (July 2022) - Modabber, Ali; Beckmann, Luisa; Ayoub, Nassim; Raith, Stefan; Winnand, Philipp; Heitzer, Marius; Hölzle, Frank; Ooms, Mark
Summary: Introduction: The soleus perforator flap and the peroneal perforator flap could be alternatives to the radial forearm flap for head and neck reconstruction. However, their flap dimensions remain unknown. This study aims to determine the dimensions of both flaps and allow preoperative planning for reconstruction based on clinical parameters. Materials & Methods: Computed tomography records of 296 patients dated from 2009 through 2019 were retrospectively analyzed. Virtual three-dimensional flap models of the soleus perforator flap and peroneal perforator flap were aligned to segmented leg models, and flap thickness and volume were determined. Associations of flap thickness and volume with clinical parameters were evaluated, and a calculation method was derived. Results: The soleus perforator flap had an average thickness of 8.7 mm (4.8 mm) and an average volume of 0.9 cm³ (0.5 cm³) per square centimeter surface area. The peroneal perforator flap had an average thickness of 6.4 mm (3.8 mm) and an average volume of 0.8 cm³ (0.4 cm³) per square centimeter surface area. The soleus perforator flap was thicker and more voluminous than the peroneal perforator flap (both p<0.001). For both flaps, leg circumference was the strongest predictor of flap thickness (ß=0.524, p<0.001 and ß=0.700, p<0.001, respectively) and flap volume (ß=0.535, p<0.001 and ß=0.712, p<0.001, respectively). Conclusion: Dimensions of the soleus perforator and the peroneal perforator flaps are similar to those of the radial forearm flap. Preoperative planning of flap dimensions, such as flap thickness and volume, can help the surgeons select the appropriate flap.